6 - Tribe and Tribalism in Kenya’s Politics - Anyang’ Nyong’o, Peter; Karugu, Caroline (CODESRIA Bulletin, 2023)
I already realised the problem was not just one of disagreement between political leaders over an election result: the countrywide violence meant the problem was more fundamental, arising from the makeup of the Kenyan political system and its relationship with society. We needed a process that would address the root causes of Kenya’s problems, otherwise any agreement would constitute nothing more than a delay before the next violent crisis … Our mediation needed to be the beginning of a true process of political reform. – Kofi Annan, former General, UN